Risk factors and complications associated with intra-operative or post-operative identification of a PFO in cardiac surgery patients: A cohort study - Laghlam, Driss; Coroyer, Lucas; Martial, Paul-Jun; Estagnasie, Philippe; Squara, Pierre; Nguyen, Lee S. (Frontiers in Neurology, 2023)
Introduction: It is unknown whether PFO reopening in peri-operative setting of cardiac surgery affect the risk for stroke and postoperative outcomes. Methods: We performed a single-center, retrospective study based on a prospectively collected database in a tertiary cardiac surgery center. Using logistic regression, we assessed risk factors of PFO finding around surgery and subsequent clinical complications. Results: Between January 2007 and July 2019, 11034 patients underwent cardiac surgery in our center and were included. Two hundred thirty-three patients (2.1%) presented a finding of PFO including 138 per-operative disclosure and 95 postoperative finding for hypoxemia. In whole cohort, mean age was 68.4 11.5 years old including 73.9% of men. Post-operative PFO finding was associated with more ischemic strokes compared with per-operative finding and control group (7(7.4%) vs 3(2.2%) vs 236(2.2) respectively; p=0.003). Moreover, patients with post-operative PFO reopening experienced higher rate of pneumonia, reintubation and longer length of stay in ICU. Post-operative reopening of PFO, but not per-operative finding, was independently associated with ischemic strokes (adjusted odds-ratio=3.5, 95% confidence interval (CI) 1.6-7.8; p=0.002). Other variables associated with stroke incidence included age, mitral valve surgery and ascending aorta surgery. Per- or post-operative PFO closure was associated with reduced adverse respiratory outcomes and a trend of lower cerebral ischemic event. Conclusion: PFO finding incidence in peri-operative cardiac surgery care was rare (2%) but post operative finding of PFO was associated with higher risk of ischemic strokes, worsened respiratory outcomes and prolonged hospitalization.